a) =
= 0,6.│a│
Vì a < 0 nên │a│= -a. Do đó = -0,6a.
b) =
.
= │
│.│3 - a│.
Vì ≥ 0 nên │b│=
. Vì a ≥ 3 nên 3 - a ≤ 0, do đó │3 - a│= a - 3.
Vậy =
(a - 3).
c) =
=
= √81.√16.
= 9.4.│1 - a│
Vì a > 1 nên 1 - a < 0. Do đó │1 - a│= a -1.
Vậy = 36(a - 1).
d) :
=
: (
=
: (
.│a - b│)
Vì a > b nên a -b > 0, do đó│a - b│= a - b.
Vậy :
=
: (
(a - b)) =
.
a) =
= 0,6.│a│
Vì a < 0 nên │a│= -a. Do đó = -0,6a.
b) =
.
= │
│.│3 - a│.
Vì ≥ 0 nên │b│=
. Vì a ≥ 3 nên 3 - a ≤ 0, do đó │3 - a│= a - 3.
Vậy =
(a - 3).
c) =
=
= √81.√16.
= 9.4.│1 - a│
Vì a > 1 nên 1 - a < 0. Do đó │1 - a│= a -1.
Vậy = 36(a - 1).
d) :
=
: (
=
: (
.│a - b│)
Vì a > b nên a -b > 0, do đó│a - b│= a - b.
Vậy :
=
: (
(a - b)) =
.